UPAYA PENGEMBANGAN OBJEK WISATA AIR TERJUN GURUH GEMURAI OLEH DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN KUANTAN SINGINGI - Jepriyus "; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Kuantan Singingi Regency has many potentials with various tourist objects such as natural attractions are quite interesting and reliable to be developed as a rural tourist attraction. The potential and character of the Kuantan Singingi regency as mentioned above is also supported by the Kuantan Singingi regional government policy stated in the vision and mission of Kuantan Singingi Regency in the development of regional economy.Related to the number of tourism potential owned by Kuantan Singingi Regency and the effort to realize the vision and mission of Kuantan Singingi Regency Government in the field of tourism, the government of Kuantan Singingi Regency made the regional regulation no. 18 of 2012 on tourism business, and in this regulation governing tourism issues such as tourism services business, the exploitation of tourism objects and attractions, the business of tourism facilities, the exploitation of attractions and various tourism regional economic development.The theory used is according to Suwantoro (2004: 3) Tourism is a process of temporary departure from someone or more to another place outside the residence. The term tourism is closely related to the definition of travel, ie as a change in tempaat stay for a reason and not to conduct activities that generate wages. In this study the authors used descriptive qualitative research with the location of research at the Department of Culture and Tourism Kuantan Singingi Regency and the key information is the Head of Tourism.From the results of research known that the implementation of tourism development conducted by the Department of Culture and Tourism Kuantan Singingi regency has not fully run with the maximum. This is caused by the existence of several factors that the authors encountered in the location of research that is; 1) Limitations of Funds, 2) Lack of human resources, 3) Infrastructure in supporting tourism 4) And lack of adequate support Facilities and Infrastructure.